Histone deacetylase 4 deletion broadly affects cardiac epigenetic repression and regulates transcriptional susceptibility via H3K9 methylation - Finke, Daniel; Schanze, Leonard M.; Schreiter, Friederike; Kreußer, Michael; Katus, Hugo; Backs, Johannes; Lehmann, Lorenz (Journal of molecular and cellular cardiology, 2021)
Histone deacetylase 4 (HDAC4) is a member of class IIa histone deacetylases (class IIa HDACs) and is believed to possess a low intrinsic deacetylase activity. However, HDAC4 sufficiently represses distinct transcription factors (TFs) such as the myocyte enhancer factor 2 (MEF2). Transcriptional repression by HDAC4 has been suggested to be mediated by the recruitment of other chromatin-modifying enzymes, such as methyltransferases or class I histone deacetylases. However, this concept has not been investigated by an unbiased approach. Therefore, we studied the histone modifications H3K4me3, H3K9ac, H3K27ac, H3K9me2 and H3K27me3 in a genome-wide approach using HDAC4-deficient cardiomyocytes. We identified a general epigenetic shift from a ‘repressive’ to an ‘active’ status, characterized by an increase of H3K4me3, H3K9ac and H3K27ac and a decrease of H3K9me2 and H3K27me3. In HDAC4-deficient cardiomyocytes, MEF2 binding sites were considerably overrepresented in upregulated promoter regions of H3K9ac and H3K4me3. For example, we identified the promoter of Adprhl1 as a new genomic target of HDAC4 and MEF2. Overexpression of HDAC4 in cardiomyocytes was able to repress the transcription of the Adprhl1 promoter in the presence of the methyltransferase SUV39H1. On a genome-wide level, the decrease of H3K9 methylation did not change baseline expression but was associated with exercise-induced gene expression. We conclude that HDAC4, on the one hand, associates with activating histone modifications, such as H3K4me3 and H3K9ac. A functional consequence, on the other hand, requires an indirect regulation of H3K9me2. H3K9 hypomethylation in HDAC4 target genes (‘first hit’) plus a ‘second hit’ (e.g., exercise) determines the transcriptional response.